Respuesta :
answer is
C. (-8,-5)
y - y1 = m( x - x1)
so
y + 5 = 2(x + 8)?
in this case y1 = -5, x = -8
C. (-8,-5)
y - y1 = m( x - x1)
so
y + 5 = 2(x + 8)?
in this case y1 = -5, x = -8
Answer:
Step-by-step explanation:
Alright, lets get started.
The equation is :
[tex]y+5=2(x+8)[/tex]
If this line passes any point, that point must be satisfy with the equation of this line.
So, plugging the value of point (x,y) in this equation.
Once we plug (-8, -5) in the equation :
[tex]-5+5=2(-8+8)[/tex]
[tex]0 = 0[/tex]
It means, the point (-8, -5) is stisfying the equation of line.
So the answer is (-8, -5) option C : Answer
Hope it will help :)